Communist Party of the Soviet Union - "Schapiro, Leonard" (London, 1975)
This book outlines and summarizes the early years of the experience of the Communist Party of the Soviet Union. "Short course" is an essential tool in solving understanding what, at the time, was seen as the problem of mastering Bolshevism and arming members of the party with a particular take on Marxist-Leninist theory, i.e. knowledge of the laws of social development and political struggle and served as a means of raising the political vigilance by the party and the Bolsheviks, and served as a means of raising the matter of propaganda of Marxism-Leninism on to the appropriate theoretical level.
Keywords: Communist Parties Soviet Union .